2019
DOI: 10.1038/s41598-019-49880-w
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian randomization analysis rules out disylipidaemia as colorectal cancer cause

Abstract: Dyslipidemia and statin use have been associated with colorectal cancer (CRC), but prospective studies have shown mixed results. We aimed to determine whether dyslipidemia is causally linked to CRC risk using a Mendelian randomization approach and to explore the association of statins with CRC. A case-control study was performed including 1336 CRC cases and 2744 controls (MCC-Spain). Subjects were administered an epidemiological questionnaire and were genotyped with an array which included polymorphisms associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…One plausible explanation includes the potential link between statin use and development of incident diabetes, although the risk elevations are generally slight in previous trials (44,45). It is still controversial whether dyslipidemia is directly involved in colorectal neoplastic transformation given inconsistent results from previous Mendelian randomization analyses (46–48) and other studies (25,49–51). However, our current result does not support an association between total cholesterol level and CRC risk.…”
Section: Discussionmentioning
confidence: 99%
“…One plausible explanation includes the potential link between statin use and development of incident diabetes, although the risk elevations are generally slight in previous trials (44,45). It is still controversial whether dyslipidemia is directly involved in colorectal neoplastic transformation given inconsistent results from previous Mendelian randomization analyses (46–48) and other studies (25,49–51). However, our current result does not support an association between total cholesterol level and CRC risk.…”
Section: Discussionmentioning
confidence: 99%
“…found that increased adipose triglyceride lipase is negatively correlated with the OS of CRC patients, and in vivo experiments showed that it could promote the progression of CRC by enhancing lipid mobilization or lipolysis ( 40 ), which also reflects that high serum TG level are related to the improvement of prognosis. Other studies showed that increased TG or decreased HDL-C are associated with poor prognosis in CRC ( 11 , 41 ), or not ( 13 , 42 ). However, although some studies seem to support THR as an independent protective factor for CRC patients, further exploration is needed.…”
Section: Discussionmentioning
confidence: 97%
“…It is also likely that statins (which is a drug prescribed to reduce LDL-cholesterol levels) could confound the dyslipidemia-CRC associations. Findings from prospective and MR studies of either dyslipidemia or statins with CRC risk are inconsistent in this respect (34)(35)(36)(37). Collectively, it remains to be clarified whether dyslipidemia plays a causal role in CRC development or is only a bystander.…”
Section: Discussionmentioning
confidence: 99%